Hubungan Dukungan Sosial Dan Hardiness Dengan Psychological Well-Being Pada Mahasiswa Rantau Di Universitas Pendidikan Indonesia Bandung - Melani, Ade; Ihsan, Helli; Kosasih, Ismawati (Jurnal Ilmiah Wahana Pendidikan, 2024)
are a group of individuals who are vulnerable to experiencing low levels of psychological well-being. Previous research suggested the possibility that social support and hardiness could increase the psychological well-being of those students. Therefore, the purpose of this study was to examine whether or not there is a link between social support and hardiness and psychological well-being among students from Sumatera Island at the Indonesian University of Education, Bandung, West Java. The research method uses quantitative methods with correlation analysis techniques. Data was collected using the Six Dimensions of Psychological Wellbeing Scale and the Social Support Scale by both of which have been adapted to Indonesian by Fransisca (2018); and the Dispositional Resilience Scale developed by Hystad (2010). The results showed that from 100 sample that was obtained, there was a positive relationship between social support (r = 0.660, p <0.05). and hardiness (r = 0.758, p <0.05) with psychological well-being in students from Sumatera Island at the Indonesian University of Education. The results of this study show the importance of increasing social support and hardiness, in increasing the psychological well-being of overseas students as well.